Synthesis of nanocrystalline delta-MoN by thermal annealing of amorphous thins films grown on (100) Si by reactive DC sputtering at room temperature - Haberkorn, N. (2018)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina